Locked in the Cabinet - Reich, Robert B. 1946- (Knopf, 1997)
The story of the author's four years as Secretary of Labor in Clinton's first term as President of the United States.
Keywords: Reich, Robert B; Reich, Robert B. -- 1946-; Clinton, Bill -- 1946-; United States. -- Dept. of Labor -- Biography; USA -- Government; Geschichte 1992-1996; Geschichte 1992-1997; Ministers; Overheidsbeleid; Presidenten; Werkgelegenheidsbeleid; Politik; Cabinet officers -- United States -- Biography; Regierung; USA; Biografie; Erlebnisbericht; Tagebuch -- 1992-1996